Research methodology and scientific writing - Thomas, C. George (Springer ; ANE Books, 2021)
This book presents a guide for research methodology and scientific writing covering various elements such as finding research problems, writing research proposals, obtaining funds for research, selecting research designs, searching the literature and review, collection of data and analysis, preparation of thesis, writing research papers for journals, citation and listing of references, preparation of visual materials, oral and poster presentation in conferences, and ethical issues in research . Besides introducing library and its various features in a lucid style, the latest on the use of information technology in retrieving and managing information through various means are also discussed in this book. The book is useful for students, young researchers, and professionals.- Resumé vydavatel
First edition published by ANE Books, India.
Keywords: vědecký výzkum -- metodologie; odborné texty; vědecká činnost; technické vzdělávání; scientific research -- methodology; professional texts; scientific activities; technical education; akademické psaní; elektronické knihy; příručky; electronic books; handbooks and manuals